Effects of Season and Agro-Ecological Zone on the Microbial Quality of Raw Milk along the Various Levels of the Value Chain in Uganda - Grimaud, Patrice; Sserunjogi, Mohamed; Wesuta, Milton; Kato, Moses; Faye, Bernard (Tropical Animal Health and Production, 2009)
Dairy production in Uganda is pasture-based and traditional Ankole cattle make up 80% of the cattle herd, reared in both pastoral and agro-pastoral ecological zones. Regardless of the zone, milk quality is lowest in production basin during the dry season when ambient temperatures are highest and water is scarce. Poor hygiene and quality management contributed to the deterioration of raw milk quality during its storage and delivery to the final consumer, and concealed the seasonal effect when milk reached urban consumption areas. Poor milk quality is a challenge for the Ugandan Dairy Development Authorities who wish to make the milk value chain safe. This study provides baseline information for the implementation of an HACCP-based system to ensure the hygienic quality of milk from the farm to the market place.
Keywords: Microbial contamination . Quality insurance . Raw milk . Uganda